Dia2 controls transcription by mediating assembly of the RSC complex. - Edward J Andress; Roman Holic; Mariola J Edelmann; Benedikt M Kessler; Veronica P C C Yu (PLoS ONE)
Background Dia2 is an F-box protein found in the budding yeast, S. cerevisiae. Together with Skp1 and Cul1, Dia2 forms the substrate-determining part of an E3 ubiquitin ligase complex, otherwise known as the SCF. Dia2 has previously been implicated in the control of replication and genome stability via its interaction with the replisome progression complex. Principal findings We identified components of the RSC chromatin remodelling complex as genetic interactors with Dia2, suggesting an additional role for Dia2 in the regulation of transcription. We show that Dia2 is involved in controlling assembly of the RSC complex. RSC belongs to a group of ATP-dependent nucleosome-remodelling complexes that controls the repositioning of nucleosomes. The RSC complex is expressed abundantly and its 17 subunits are recruited to chromatin in response to both transcription activation and repression. In the absence of Dia2, RSC-mediated transcription regulation was impaired, with concomitant abnormalities in nucleosome positioning. Conclusions Our findings imply that Dia2 is required for the correct assembly and function of the RSC complex. Dia2, by controlling the RSC chromatin remodeller, fine-tunes transcription by controlling nucleosome positioning during transcriptional activation and repression.